Effectiveness of Ethno-Inquiry-Interactive Physics Multimedia Using the Gopa Game to Improving Students’ Numeracy Literacy - Nurjumiati Nurjumiati; Syahriani Yulianci; Nurhairunnisah Nurhairunnisah; Suriya Ningsyih (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2026)
This study aims to analyze the effectiveness of ethno-inquiry-based interactive physics multimedia through the traditional Gopa game in improving students' numeracy in parabolic motion material for grade XI of high school. This study used a quasi-experimental method with a pretest-posttest control group design involving two classes, namely the experimental class that used ethno-inquiry-based interactive multimedia through the Gopa game and the control class that used conventional learning. The research instrument included a numeracy literacy test. Data were analyzed using an independent t-test and N-Gain test calculations to measure the level of effectiveness. The results showed that there was a significant difference between the numeracy and cultural literacy results of students in the experimental and control classes. With an Independent Sample t-test on the posttest score, there was a significant difference between the experimental and control classes with a p-value of 0.029 (p <0.05). The average posttest score of the experimental class (74.92) was higher than the control class (64.67). These results indicate that the use of ethno-inquiry-based interactive multimedia in the Gopa game has a positive influence on improving students' numeracy literacy. The average gain in numeracy literacy scores in the experimental and control classes was in the moderate category, meaning that the effectiveness of using ethno-inquiry-based interactive physics multimedia through the Gopa game on parabolic motion material was categorized as moderate or quite effective.